The Progress a Pre-Service English Language Teacher Made in Her Feedback Giving Practices in Distance Teaching Practicum - Koşar, Gülten (JET (Journal of English Teaching), 2021)
As a result of the COVID-19 pandemic, teaching practicum has been conducted in online learning settings in Turkey, which, in return, has made pre-service English language teachers do their practicums online. The lack of research into the effect of distance teaching practicum on pre-service English language teachers’ practices of giving feedback prompted the researcher to carry out this research. This instrumental case study aims to investigate the changes in a pre-service English language teacher’s feedback giving practices in the English lessons she taught in the distance teaching practicum and her views about how the distance teaching practicum affected her skills of providing feedback. The results obtained from the analysis of the data collected from the researcher’s notes on the pre-service English language teacher’s provision of feedback in the four online lessons she taught, post-lesson telephone interviews and end-of-study semi-structured interview indicated her teaching experiences helped her make a considerable progress in her skills in giving effective feedback. The findings pointed to the significance of distance teaching practicum in developing pre-service English language teachers’ feedback giving practices.